(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Opportunistic infections represent a significant clinical challenge in immunocompromised populations, with mortality rates reaching 35-40% in severely affected individuals. This study examines the epidemiological patterns and clinical manifestations of opportunistic infections across 847 immunocompromised patients over a 36-month period. Fungal infections predominated at 42.3%, followed by viral (31.7%) and bacterial (26.0%) etiologies. HIV-positive patients demonstrated the highest infection burden (68.4%), while solid organ transplant recipients showed distinct pathogen profiles. These findings underscore the necessity for targeted prophylactic strategies and improved diagnostic protocols in high-risk populations.